2010
DOI: 10.1143/jjap.49.05fa12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Desorption from SiO2 Substrates on the Thickness of Manganese Oxide Diffusion Barrier Layer Formed by Chemical Vapor Deposition

Abstract: Hysteresis in the field effect of bilayer graphene is observed at a low temperature. We attribute this effect to charge traps in the substrate. When the sweep rate of the back-gate voltage is increased to higher values, the hysteresis becomes more pronounced. By measuring the hysteresis in the field effect, the lifetime of the charge traps is estimated as 16.9 min. It is shown that the influence of charge traps on graphene is strongly affected by a magnetic field. Above 5 T the hysteresis remains constant.Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Based on these considerations, Neishi et al [12] and Matsumoto et al [14], [15] reported the deposition behavior and diffusion barrier property, as mentioned already. However, the diffusion barrier property was examined only with an EDS, which is not capable of detecting the small amount of elements of less than 0.1 at%.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on these considerations, Neishi et al [12] and Matsumoto et al [14], [15] reported the deposition behavior and diffusion barrier property, as mentioned already. However, the diffusion barrier property was examined only with an EDS, which is not capable of detecting the small amount of elements of less than 0.1 at%.…”
Section: Introductionmentioning
confidence: 69%
“…The deposited layer was tentatively indicated as MnO x . The thickness of the amorphous layer could be controlled by changing deposition temperature [12] and by absorbed moisture in tetraethyl orthosilicate (TEOS)-SiO 2 substrates [14]. A conformal deposition of the thin MnO x layer was also possible in high-aspect-ratio contact holes [15].…”
Section: Introductionmentioning
confidence: 99%
“…The as-deposited films (referred to as pristine) have different pore size and porosity as described in the Table I. As reported in the litterature, 4 to form a thin MnO x layer, moisture desorbing from the substrate is needed to participate in the hydrolysis reaction of the Mn precursor during the CVD process. For this purpose, to increase the amount of adsorbed water by a controllable way, the films were subjected to O 2 plasma during 200 sec (inductively coupled plasma chamber -ICP) * Electrochemical Society Active Member.…”
Section: Methodsmentioning
confidence: 99%
“…For further technology scaling, Chemical Vapor Deposition (CVD) of Mn has been investigated using Mn-amidinate and more predominately using Bisethylcyclopentadienyl manganese, (EtCp) 2 Mn precursors. [1][2][3][4] For both precursors, the barrier properties of CVD-Mn-based layers were also studied and proven on dense SiO 2 substrates. 1,2 However, if CVD-Mn-based barriers must be used in advanced technologies, it has to be formed on porous SiCOH low dielectric constant (low-k) materials in order to satisfy signal transmission speed needs within the chip.…”
mentioning
confidence: 99%
“…However, we reported previously that the presence of absorbed water in dielectrics has notable effects on the structure, composition, and thickness of the CVD-grown MnO x layer [8][9][10]. Since the amount of the absorbed water is difficult to control, a new MnO x forming process should be developed so as not to be influenced by the absorbed water in the dielectric substrates.…”
Section: Introductionmentioning
confidence: 99%